Gold Nanoparticle-Based Optical Probe for Screening Hexaconazole Rapidly - Bai, L.Y.; Zhang, Y.P.; Chen, J.; Tao, J.Z.; Chen, N.; Zhou, X.M. (Asian Journal of Chemistry, 2011)
Gold nanoparticles (Au NPs) were synthesized by reduction of hydrogen tetrachloroaurate and used as a facile and highly selective sensor for the visual detection of hexaconazole. The presence of hexaconazole could rapidly induce the aggregation of gold nanoparticles, thereby resulting in red-to-blue (or purple) colour change. The concentration of hexaconazole was determined by the naked eye visually and could further be monitored by an UV-VIS spectrometer with a limit of detection (LOD) about 0.7 × 10-6 mg/L. The highest selectivity was proved in comparison with other eleven pesticides and the sensitivity and dynamic range of the colorimetric signals could be adjusted by the addition of NaCl or changing pH in gold nanoparticles.